Architectural drawing - Dernie, David (Laurence King Publishing, 2014)
"This book focuses on the exciting possibilities for representing the built environment with techniques ranging from pencil sketching to computers. It teaches students the following skills: how to draw using a range of media, the basic rules of making effective spatial images, and how to express ideas through appropriate media and forms of communication. Following a revised and expanded introduction, the book is divided into three sections: Media, Types, and Places. Each section is illustrated with exemplary drawings and accompanying commentaries. Step-by-step sequences and practical tips will further help students to make the most of their newly acquired skills. The second edition includes more on a variety of techniques, particularly digital, and new artworks from practicing architects, making it an indispensable practical and inspirational resource."--Provided by publisher